The elderly teachers of Cabanatuan City their lifestyles and lifestyle correlates (2003)
The study aimed to point out that the lifestyle elderly teachers lead their lives could make them live longer, be more productive, and functional even at the height of their diminishing vigor and vitality in the aspect of health. Gathered data were structured and analyzed using descriptive statistics. Results about their socio-economic characteristics showed that majority of the elderly teachers were women, married, have derived income of Php11,775.00, with three mean number of children, and Catholics. Their social interaction, emotional maturity, work-related activities, spirituality and reflections showed that these were relatively favorable to health; their well-being showed indications that they were physically fit, socially interactive, emotionally matured, occupationally satisfied and fulfilled and, spiritually well. Their lifestyle preferences in grooming and personal care, food habits and preferences, and recreation and leisure were found to be correlates of their physical fitness, social interaction, emotional maturity, spirituality and reflections. Their home condition and mobility indicated that majority (57.5%) were residents of Cabanatuan City with (32.%) 3-bedroom, concrete homes (47.5%) acquired thru their own personal resources and were reported to have (67.5%) 2 to 3 household members.
Keywords: Teachers -- Lifestyles